Community participation as a right in law - KIBOI, Maryanna Wangare (KDI School, 2017)
Effective community participation provides a platform for all concerned stakeholders to present different opinions, concerns and priorities (environment, social or economic) with respect to a particular development project and work together to find a common sustainable ground. In such cases not only can potential problems be identified and resolved but ideas, knowledge, options, solutions can be exchanged and exhausted in an effort of finding human to human and human to ecosystem equilibrium. There is no doubt that community participation plays a significant if not the main role in maintaining a balance between economic development, environmental protection and social development that leads us to the end point of sustainable growth. This paper will not attempt to analyze the effects of community participation or its benefits and add to the pile of studies that have already done this. Instead, it will examine the status of participation under Kenyan law to establish whether effective community participation is secured by the law. Further, an attempt will bemade to determine whether effective community participation is being implemented by examining various cases of development projects. The study is limited to water and dam projects in Kenya.
Thesis(Master) --KDI School:Master of Development Policy,2017